PENERAPAN LINGKUNGAN ALAM SEKITAR PADA MATERI KEANEKARAGAMAN HAYATI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V SD NEGRI 18 BANDA ACEH - sumiati, Desi Renika; Fita Nelyza; Ruslaini, Ruslaini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of utilizing the surrounding natural environment in biodiversity learning materials on the learning outcomes of fifth-grade students at SDN 18 Banda Aceh. The study employed a quantitative approach using a One-Group Pretest–Posttest Design and involved 32 students as participants. The results showed that the mean pretest score of 52.12 increased to 85.62 on the posttest, with an N-Gain score of 0.70, indicating a high improvement category. The hypothesis testing results revealed a significance value of 0.000 < 0.05, indicating that the utilization of the surrounding natural environment had a significant effect on students' learning outcomes. In addition, students' responses to the learning process were classified as very positive, with a percentage score of 85.65%. Therefore, the use of the surrounding natural environment is effective in improving students' learning outcomes in biodiversity learning materials.